27 The Neurohistology Of Painful And Pain-free Rotator Cuff Tendons. (5th September 2014) - Dean, Benjamin; Franklin, Sarah; Murphy, Richard; Benson, Richard; Wheway, Kim; Watkins, Bridget; Javaid, Kassim; Carr, Andrew
Abstract : Introduction: The relationship between rotator cuff tendon structure and pain symptoms is imperfect and icompletely understood. 2 The inability to gather tendon-matched and age-matched control tissue from live donors has been a significant limiting factor in many previous studies. 1 The aim of this study was to determine whether there were neurohistological differences between painful and pain-free rotator cuff tendons. Methods: Supraspinatus tendon specimens were obtained by ultrasound guided biopsy from 9 patients with painful rotator cuff tendinopathy (RCT) resistant to conservative management (painful group) and 9 pain-free patients at over 6 years following subacromial decompression (SAD) (pain-free group). Pain symptoms were measured using the validated Oxford Shoulder Score (OSS). Structural tendon integrity was assessed ultrasonographically. Basic histological staining and immunohistochemistry was performed. Mann-Whitney U tests were used to test for differences between groups. Results: The groups were similar in terms of age, sex and structural tendon abnormality. The painful group consisted of 7 males and 2 females, the pain-free group of 6 males and 3 females. The mean age of the painful group was 51 years and that of the pain-free group was 52 years. The median OSS in the painful group was 32 (range 23 to 36) and this was significantly lower (p = 0.0002) than the median OSS in the pain-free group (all 48). There were two partial thickness tears in both groups and no full thickness tears. There were no significant differences between groups in terms of cellularity, vascularity, proliferation and hypoxia inducible-factor 1α expression. The leucocyte count (% of CD45 positive cells) and macrophage count (% of CD206 positive cells) were increased in the painful group versus pain-free (p = 0.038 and 0.0004 respectively). The expression of metabotropic glutamate receptor 7 (mGluR7) was reduced in the painful group versus pain-free (p = 0.002), while the expression of the Kainate 1 receptor was increase in the painful group (p = 0.003). PGP 9.5 (a nerve marker) and Lactate Dehydrogenase (LDH) expression were increased in the painful group versus pain-free (p = 0.008 and 0.007 respectively). There were no significant differences in glutamate, the inotropic glutamate receptor (NMDAR1) and the metabotropic glutamate receptors (mGluR1 and 2) between groups. Discussion: This study has shown that specific characteristics of tendon neurohistology are associated with the presence of shoulder pain. This provides strong evidence that the rotator cuff tendon is of key importance in the symptomatology of RCT. The mechanism behind these tendon differences is unclear. These findings are novel and improve our understanding of pain in RCT, and may help provide novel therapeutic targets. References: 1 Dean BJ, Franklin SL, et al . A systematic review of the histological and molecular changes in rotator cuff disease. Bone Joint Res . 2012;1(7):158–166 2 Yamaguchi K, D. K. et al . The demographic and morphological features of rotator cuff disease. A comparison of asymptomatic and symptomatic shoulders. JBJS (Am) . 2006;88(8):1699–1704